Time-dependent entropy of a cooling Bose gas - Wolschin, Georg (epl, 2020)
Exact analytic solutions of a nonlinear boson diffusion equation with suitable initial conditions that account for evaporative cooling of ultracold atoms, plus boundary conditions at the singularity is an element of = mu < 0 are presented, and used to calculate the time-dependent entropy of a cold quantum gas. Copyright (C) EPLA, 2020
Gesehen am 24.07.2020